Design, analysis, and realisation of chipless RFID tag for orientation independent configurations. Issue 5 (18th May 2020) - Hashmi, Mohammad S.; Sharma, Vijay
Abstract : The architectures of two innovative compact orientation independent chipless radio frequency identification device (RFID) tags for emerging applications such as the internet of things are presented. These tags, when illuminated, generate resonant frequencies in the radar cross‐section backscattered spectrum, which are used to encode the data. These are based around L‐type resonators, which can be read from front and back using linear polarisation waves as they do not have the ground plane. The first tag design consists of L‐resonators in the lower triangular of the substrate, and thereby mutual coupling is increased as a reduction in the size. The second tag design incorporates alternate L‐resonators in both halves of the substrate and exhibits reduced mutual coupling and enhanced printing strength but with a reduction in bit density. The proposed concept is demonstrated through prototypes of 8‐bit chipless tags on Rogers substrate. These tags require very low bandwidth to encode 8‐bit and occupy a small board size of 20 mm × 20 mm, and these are considerable improvements in the development of chipless RFID.